Subalternity and the Mummifification of Culture in Gramsci’s “Prison Notebooks” - Jackson, Robert (International Gramsci Journal, 2023)
Gramsci’s concept of mummification is rarely remarked upon in the literature and has not received the systematic treatment afforded to other concepts in his lexicon. Locating the term in the semantic field of subalternity, this article explores the connection between mummification and passivity. The origins and development of the concept of mummification are traced in Gramsci’s thought, suggesting an important role in explaining the passive constitution of the subaltern. Mummification describes an embalming process through which certain forms of culture, positive and legitimate when created, become degenerate through a process of repetition in changed circumstances. The dual nature of mummification is examined, imposed from above through strategies of dispersion wrought by the dominant groups, or emerging from below through the ‘intellectual laziness’ characteristic of ‘Lorianism’. The different terrains upon which the term is used in the Prison Notebooks are analysed (parties, social groups, common sense, culture), proposing that these aspects of mummification are ultimately ‘translatable’ aspects of a unitary phenomenon. It is argued that the concept of mummification helps to articulate the intimate relationship between the dialectical poles of hegemony and subalternity in Gramsci’s thought. The concept is able to perform a critical function by making an incision between forms of culture that are historically opportune and those that are anachronistic, the reactionary form of the ‘living dead’. In our crisis-ridden situation, of zombie banks and vampire capital, this study of mummification is a timely consideration of the Sardinian thinker’s contribution to these themes of political monstrosity.